Preovulatory Aging In Vivo and In Vitro Affects Maturation Rates, Abundance of Selected Proteins, Histone Methylation Pattern and Spindle Integrity in Murine Oocytes - Demond, Hannah (PLoS One, 2016)
Delayed ovulation and delayed fertilization can lead to reduced developmental competence of the oocyte. In contrast to the consequences of postovulatory aging of the oocyte, hardly anything is known about the molecular processes occurring during oocyte maturation if ovulation is delayed (preovulatory aging). We investigated several aspects of oocyte maturation in two models of preovulatory aging: an in vitro follicle culture and an in vivo mouse model in which ovulation was postponed using the GnRH antagonist cetrorelix. Both models showed significantly reduced oocyte maturation rates after aging. Furthermore, in vitro preovulatory aging deregulated the protein abundance of the maternal effect genes Smarca4 and Nlrp5, decreased the levels of histone H3K9 trimethylation and caused major deterioration of chromosome alignment and spindle conformation. Protein abundance of YBX2, an important regulator of mRNA stability, storage and recruitment in the oocyte, was not affected by in vitro aging. In contrast, in vivo preovulatory aging led to reduction in Ybx2 transcript and YBX2 protein abundance. Taken together, preovulatory aging seems to affect various processes in the oocyte, which could explain the low maturation rates and the previously described failures in fertilization and embryonic development.